IP based network public address for intelligent building environment - Chui, Yew Leong; Ramli, Abdul Rahman; Perumal, Thinagaran (Science and Engineering Research Support Society, 2014)
IP based network public address (PA) is an audio management system that provides high flexibility in reconfiguration, system expansion, and requires much simplified cabling structure. This translates to significant cost saving in installation cost, both labour and material, as it requires less cabling, reduced cable size, conduit size, and trunking size. The network PA works very much similarly to computer networks where packets of data are transmitted from one node to another with each of them having a unique IP address in the network system. The nodes will then only pick up the packets that solely addressed to them. The network PA can also be integrated with other building services or subsystems that are TCP/IP compliant such as the fire alarm management system, CCTV system, and building management system to provide instantaneous voice assisted response and feedback from each system.